Clinical manifestations of human leptospirosis: bacteria matter - Rajaonarivelo, Jeanne Arline; Desmoulin, Anissa; Maillard, Olivier; Collet, Louis; Baudino, Fiona; Jaffar-Bandjee, Marie-Christine; Blondé, Renaud; Raffray, Loïc; Tortosa, Pablo (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction A high incidence of human leptospirosis is recorded on Mayotte, an oceanic island located in southwestern Indian Ocean, but the severity of the disease appears relatively mild in terms of mortality rate and admission to the intensive care unit. It has been proposed that mild leptospirosis may result from a limited virulence of some of the occurring Leptospira species to which the population is exposed. Methods Clinical and biological data of patients admitted to the Centre Hospitalier de Mayotte were collected and the infecting Leptospira species were determined through molecular typing. Results Leptospira interrogans was detected in the minority of admitted patients but most of these patients suffered from severe forms, with 50% admitted to intensive care unit and suffering from organ failures. Nineteen percent of patients infected with Leptospira borgpetersenii were admitted to the intensive care, with 13% displaying organ failures, and one patient died. Leptospira mayottensis was found in 28% of the patients and not a single severe case was observed. Discussion The distribution of Leptospira species in patients was not different from that reported 10-15 years ago and bacterial genotypes were very closely related to those previously reported. These results highlight the importance of the diversity of pathogenic Leptospira circulating on Mayotte island and are in keeping with distinct outcome of the disease depending on the infecting Leptospira. Altogether, presented data support that the infecting Leptospira species is an important driver of disease severity in humans.